Job Shop Layout Improvement with Simulation Technique: A Case of Metal Sheet Production - Wimalin Laosiritaworn (2020)
© 2020 IOP Publishing Ltd. All rights reserved. This paper investigates the improvement of job shop layout with simulation technique. A case study of Siam GN metal sheet, the manufacturer of customized metal sheet products was used. The objective is to increase production efficiency and reduce materials handling distance and time. Data regarding product and machine type were collected. CORELAP (Computerized Relationship Layout Planning) and Group technology based on ROC (rank order clustering) algorithm were applied to design the improved layouts. ARENA software was used to simulate the new layout from both techniques. The simulation show that CORELAP layout reduce production time by 17.12% while group technology layout reduces materials handling time by 11.41%. CORELAP layout therefore, was chosen for implementation. Simulation techniques allows user to experiment with different scenario hence selecting the most appropriate one without interfering with the actual process.